2022
DOI: 10.3390/mti6070051
|View full text |Cite
|
Sign up to set email alerts
|

Is Natural Necessary? Human Voice versus Synthetic Voice for Intelligent Virtual Agents

Abstract: The use of intelligent virtual agents (IVA) to support humans in social contexts will depend on their social acceptability. Acceptance will be related to the human’s perception of the IVAs as well as the IVAs’ ability to respond and adapt their conversation appropriately to the human. Adaptation implies computer-generated speech (synthetic speech), such as text-to-speech (TTS). In this paper, we present the results of a study to investigate the effect of voice type (human voice vs. synthetic voice) on two aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…Qualitative feedback collected in this study indicated that three participants found ERICA's voice robotic and that this contributed to their low ratings of ERICA on the SRS scale. In a recent study investigating the impact of ECA voice types on likeability and user-agent relationships, users were reported to prefer a human voice over text-to-speech synthesis, but this preference did not appear to interfere with their user-agent relationship or interaction outcomes [61]. TTS voices continue to improve, but if outcomes are negatively impacted in future studies, we can record a human voice to speak ERICA'S dialogue, though this makes adaptive dialogue difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative feedback collected in this study indicated that three participants found ERICA's voice robotic and that this contributed to their low ratings of ERICA on the SRS scale. In a recent study investigating the impact of ECA voice types on likeability and user-agent relationships, users were reported to prefer a human voice over text-to-speech synthesis, but this preference did not appear to interfere with their user-agent relationship or interaction outcomes [61]. TTS voices continue to improve, but if outcomes are negatively impacted in future studies, we can record a human voice to speak ERICA'S dialogue, though this makes adaptive dialogue difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as face-to-face communication has been identified as an important factor in encouraging treatment adherence, which is supported by the embodied nature of ECAs [35]. Furthermore, a sense of co-presence can be achieved with virtual agents [36,37].…”
Section: Ecas In Healthcare and Strokementioning
confidence: 97%
“…Görme yetersizliği olan geniş katılımcılı bir hedef kitlede etkileşim öğelerinin artırıldığı, öğrenci projelerinin işe koşulduğu iyi yapılandırılmış bir ters yüz öğrenme modelinin etkililiği incelenebilir. Akıllı ses ajanlarının seslendirme kalitesi arttıkça insan sesiyle benzer performanslar sergilediği görülmektedir (Abdulrahman ve Richards, 2022). Araştırmada kullanılan makine sesi zaman zaman harf ve seslendirme hataları yapabilmekte ve insan sesinden uzaklaşabilmektedir.…”
Section: öNerilerunclassified